Examining trajectories of nonsuicidal self-injury across the first year of university - Farrell, Brooke C.T.; Ewing, Lexi; Hamza, Chloe A. (Journal of affective disorders, 2024)
Nonsuicidal self-injury (NSSI) is prevalent among emerging adults in post-secondary school, but little is known about change and stability in NSSI during the transition to university. Moreover, there has been limited person-centered work focusing on heterogeneity in NSSI engagement among students over time. The present study aimed to investigate the development and maintenance of NSSI across the first year of university and explore predictors of potential variability in trajectories of NSSI. The present sample consisted of 1125 first-year university students at a large post-secondary institution (Mage = 17.96, 71 % female, 28 % male, 1 % gender diverse) who participated in a larger longitudinal study. Participants completed an online survey three times over their first year of university. Latent growth curve modeling (LGCM) in Mplus was utilized to explore different NSSI group trajectories across first year university. NSSI was prevalent among first year students (35 %). LGCM revealed one developmental trajectory; NSSI engagement decreased across the first year of university. Students who engaged in NSSI had increased difficulties with emotion regulation, lower self-compassion, and lower levels of social support compared to students who did not engage in NSSI. The present study may be subject to recall errors and future studies should include more gender diverse samples to increase generalization of findings. Findings highlight the transition to university as a peak period of vulnerability for NSSI engagement and emphasize the need for proactive university intervention efforts to mitigate risk and improve student well-being. •Trajectories of nonsuicidal self-injury (NSSI) were examined among young adults.•Although NSSI was prevalent, only one trajectory of NSSI over time was identified.•NSSI engagement decreased among young adults across the first year of university.•Emotion regulation, self-compassion, and social support were relevant risk factors.•Implications for student mental health research and practice are discussed.